Spotlight on the NLRP3 inflammasome pathway - Groslambert M; Py BF (Dove Medical Press, 2018)
Marine Groslambert,1–5 Bénédicte F Py1–5 1Centre International de Recherche en Infectiologie (CIRI), Université de Lyon, Lyon, France; 2INSERM, U1111, Lyon, France; 3Ecole Normale Supérieure de Lyon, Lyon, France; 4Centre International de Recherche en Infectiologie, Université Lyon 1, Lyon, France; 5CNRS, UMR5308, Lyon, France Abstract: Inflammation is triggered by a repertoire of receptors detecting infections and damages. Some of these receptors directly bind microbial ligands, while others recognize endogenous molecules exposed under stress conditions, including infections. Most of these receptors can be engaged by a relatively limited number of stimuli. Differently, NLRP3 acts as a broad sensor of cell homeostasis rupture and can be activated downstream of a plethora of stimuli. NLRP3 then assembles a multiprotein platform resulting in caspase-1 activation, which controls, by direct cleavage, the maturation of cytosolic pro-cytokines including pro-interleukin-1β. In addition, caspase-1 processes cytosolic gasdermin-D and unleashes its pore-forming N-terminal domain, leading to the release of mature cytosolic cytokines and alarmins, as well as pyroptotic cell lysis. Accumulating evidences of the aggravating role of NLRP3-mediated inflammation in various highly prevalent human conditions, including diabetes, neurodegenerative and cardiovascular diseases, raises a huge clinical interest. Nevertheless, the molecular mechanism governing NLRP3 activation remains insufficiently understood. In line with the detrimental consequences of NLRP3 activation illustrated by the aforementioned pathologies, this process is tightly regulated. In this review, we address the current understanding of the control of NLRP3 activity which can be divided into two coordinated processes referred to as priming and activation. In particular, we detail the emerging role of NLRP3 post-translational modifications critical in inflammasome assembly regulation. Keywords: inflammation, NLRP3, inflammasome, post-translational modifications